Promoting Grade 9 mathematics teachers' TPACK development through planning algebra lessons that integrate technology in Oshakati education circuit - Angula, Mechtilde (Rhodes University, Faculty of Education, Department of Secondary and Post-School Education)
The revised curriculum in Namibia highlights the integration of digital tools to help learners understand mathematics better. For this purpose, teachers need to possess Technological Pedagogical Content Knowledge (TPACK) to utilize technology effectively. However, using technology by itself does not guarantee better learning rather, it requires an understanding of how to integrate technology in teaching mathematics. Therefore, this case study explored Grade 9 mathematics teachers' TPACK development through planning algebra lessons that integrate technology. An interpretive paradigm, supported by a pragmatic paradigm, underpins the study, and a qualitative case study approach was employed. The study purposively engaged ten Grade 9 mathematics teachers from four schools in Namibia. Demographic questionnaires, Semi-structured interviews, Reflective journals, notes from discussions, focus group interviews and document analysis were used to gain teachers' insights on TPACK development. The study was guided by two educational theories: Bernstein's Sociology of Education (1971) and Bloom's Taxonomy of the Cognitive Domain (1956). Also, Mishra and Koehler's TPACK framework (2009) was used to analyze the data. The findings showed that mathematics teachers had a positive view of technology integration in mathematics lessons and TPACK development through technology-integrated lesson planning, but they lacked the knowledge for planning lessons that integrate technology. Taking part in the intervention improved the selected mathematics teachers' understanding of TPACK, making them more confident about using technology in their teaching. The study also found different strategies to help teachers incorporate technology into their lessons, along with having a strong grasp of the subject and effective teaching methods. Based on these findings, it is suggested that in-service mathematics teachers take part in interventions focused on integrating technology into lesson planning. These interventions should demonstrate how technology can improve mathematics education and how it fits with both content and teaching methods. It is also recommended that these interventions emphasize the importance of Bloom's Taxonomy in using technology for mathematics education. The study concludes by suggesting further research on how planned lessons can be implemented in actual mathematics classrooms.
Keywords: Algebra-- Study and teaching (Secondary)-- Namibia Oshakati; Technological Pedagogical Content Knowledge; Educational technology; Education Social aspects-- Namibia; Culturally relevant pedagogy-- Namibia